256 THE DEVELOPMENT OF A PATIENT AND CARER INFORMATION LEAFLET FOR PATIENTS FOLLOWING HIP FRACTURE. (25th October 2022) - Rafferty, M; Murphy, D; Creech, J; Dukelow, T; Ahern, E
Abstract: Background: Consistent delivery of high-quality information to family and caregivers can significantly improve patient experience and care during and after hospital admission. This became especially important with limited visiting hours during the COVID pandemic and our unit noted the need for appropriate written information. We aimed to complete a search of available resources nationally and internationally and develop our own information pack for distribution to our patients. Methods: Literature search was conducted for available patient and carer information resources nationally and internationally including grey literature search. Key areas and patient priorities were identified. We then began developing a patient information booklet for distribution in our unit. Results: We identified several key areas to be included in our information pack including what to expect during the hospital admission. This included pre-operative care, operative management, post-operative care especially delirium, pain, nutrition and continence promotion. Information regarding post-discharge care including off-site rehabilitation, rehabilitation at home and future actions including bone health and falls prevention interventions with home modification advice was also included. We developed a patient and caregiver information leaflet for our unit using data from the Irish Hip Fracture Database and our local unit practices and pathways to ensure information was relevant to our patients. Conclusion: We completed the design of a patient and caregiver information leaflet highlighting important aspects of care post hip fracture in our unit.